Comparison of biological indicators and umami‐related compounds in the gonad and abdomen meats of Eriocheir sinensis during different fattening periods under salinity. (17th September 2020) - Wang, Shuai; He, Yu; Wu, Xugan; Cong, Jiaojiao; Wu, Junhao; Diao, Haifeng; He, Bin; Han, Zhi
Abstract: Chinese mitten crabs ( Eriocheir sinensis ) were collected after different periods of fattening under salinity (9‰): 0, 15, 30, 45 and 60 d, corresponding to the original phase (OP), initial phase (IP), middle phase (MP), late phase (LP) and final phase (FP) respectively. Biological indicators, proximate composition, free amino acids and flavour nucleotides were determined. The results show that the gonadosomatic index was increased for both genders during fattening, and the higher content of crude protein and lipid was found in IP and MP. The content of free amino acids and umami intensity were significantly higher in most edible tissues than in the overall samples. The contents of flavour nucleotides first increased with fattening time and then decreased in the later phases. However, in female crabs, the content of 5'‐inosine monophosphate increased significantly in LP and FP compared with other phases. The findings indicate that fattening under salinity can increase gonadal index and umami intensity in E. sinensis .